Fetal growth restriction and a single umbilical artery are independent predictors of hypospadias during pregnancy. (December 2022) - Endo, Toyohide; Iida, Miho; Ichihashi, Yosuke; Oishi, Maki; Ikenoue, Satoru; Kasuga, Yoshifumi; Sato, Takeshi; Hida, Mariko; Ishii, Tomohiro; Asanuma, Hiroshi; Hasegawa, Tomonobu; Tanaka, Mamoru; et al.
Abstract: Introduction: Little is known about the association between hypospadias and small fetuses, as well as the pathological implications of fetal growth restriction (FGR). Thus, we aimed to investigate the association between hypospadias and small fetuses using a database of fetal ultrasound and obstetric events. Methods: A cohort of male singleton infants delivered after 22 weeks of gestation at Keio University Hospital between 2013 and 2019 was retrospectively reviewed. FGR was defined according to the Delphi criteria. Logistic regression analysis was performed to identify the significant predictors of hypospadias. Placental pathology was reviewed in cases with hypospadias. Results: Of the 2, 040 male infants included in the present study, 23 had hypospadias. The prevalences of a single umbilical artery (SUA), small for gestational age, maternal hypertensive disorders of pregnancy, and a small placenta, were significantly higher in infants with hypospadias. Multiple logistic regression analysis revealed that FGR (odds ratio [OR] = 9.39; 95% confidence interval [CI], 2.50–35.3) and the presence of a SUA (OR = 33.4; 95% CI, 8.00–139.5) were independently and significantly associated with hypospadias. When FGR was stratified by the time of onset, its association with hypospadias was significant regardless of the time of onset. Moreover, placental histological findings suggested that fetal vascular malperfusion might play a role in hypospadias. Discussion: FGR and SUAs are independent prenatal predictors of the development of hypospadias, and fetal vascular malperfusion of the placenta may be involved in the etiology of hypospadias. Highlights: Fetal growth restriction is an independent predictor of hypospadias development. Single umbilical artery is another independent prenatal predictor of hypospadias. Both can be diagnosed by prenatal ultrasound. Both might be associated with fetal vascular malperfusion of the placenta.